NQPC-02 Long-term survival in patients with primary intracranial germ cell tumors treated with surgery, platinum-based chemotherapy, and radiotherapy: a single-institution study. (28th November 2020) - Motomura, Kazuya; Shimizu, Hiroyuki; Ohka, Fumiharu; Aoki, Kosuke; Tanahashi, Kuniaki; Hirano, Masaki; Chalise, Lushun; Nishikawa, Tomohide; Yamaguchi, Junya; Yoshida, Jun; Natsume, Atsushi; Wakabayashi, Toshihiko
Abstract: Purpose: In the present study, we performed a retrospective review of patients receiving carboplatin based chemotherapy followed by radiotherapy for newly diagnosed primary intracranial germ cell tumors. In order to identify an optimal germ cell tumor treatment strategy, we evaluated treatment outcomes and toxicity and compliance. Methodology: This study included 110 consecutive patients with newly diagnosed primary intracranial germ cell tumors. The drug doses and administration schedule of carboplatin-etoposide (CARB-VP) were as follows: carboplatin (300 mg/m2 daily for 1 days), and etoposide (100 mg/m2 on days 1 to 3). Ifosfamide-carboplatin-etoposide (ICE) treatment comprised ifosfamide (1500 mg/m2 daily for 3 days), carboplatin (300 mg/m2 daily for 1 days), and etoposide (100 mg/m2 daily for 3 days). Patients with germinomatous germ cell tumors (pure germinoma or germinoma with STGC) basically receive three cycles of CARB-VP and a total dose of 30Gy whole ventricular radiotherapy. We delivered combination therapy consisting of combined ICE chemotherapy and craniospinal irradiation followed by the complete resection of the residual tumor for nongerminomatous malignant germ cell tumors. Results: The median follow-up time was 11.0 years (range, 0.5–37.8 years). The 5-year total survival rates of germinomatous and nongerminomatous germ cell tumors were 97.2% and 66.7%, respectively. The 10-year and 20-year total survival rates of germinomatous germ cell tumors were 95.7% and 90.0%, respectively. Adverse events related to carboplatin based chemotherapy are not detected. Furthermore, no treatment-related deaths were observed. Conclusions: Our treatment with surgery, carboplatin based chemotherapy followed by radiotherapy is effective in treating primary intracranial germ cell tumors, especially in germinomatous group.